Biomedical nanomaterials : from design to implementation - Webster, Thomas J., 1971-; Yazici, Hilal (Institution of Engineering and Technology, 2016)
Nanomaterials are able to penetrate nanoscale pores of tissues, possess prolonged circulation, enter cells, and have increased surface area per volume allowing for greater drug loading. For these reasons, nanomaterials are finding numerous uses in medicine including fighting cancer, promoting tissue regeneration, reversing aging, inhibiting infection, limiting inflammation or scar tissue growth, and many others. This book describes the engineering applications and challenges of using nanostructured surfaces and nanomaterials in healthcare. Topics covered include biomimetic coating of calcium phosphates on Ti metals; surface modifications of orthopaedic implant materials using an electroplating process; design, fabrication and application of carbon-based nano biomaterials; usage of stem cells in bone and cartilage tissue engineering; nanobiomaterials and 3D bioprinting for osteochondral regeneration; self- assembled peptide hydrogels for biomedical applications; antimicrobial properties of nanomaterials; nanoparticle enhanced radiation therapy for bacterial infection; nanomaterials used in implant technology and their toxicity; challenges of risk assessment of nanomaterials in consumer products and current regulatory status; and the clinical rationale for silicon nitride bioceramics in orthopedics. With contributions from an international selection of researchers this book is essential reading for researchers in industry and academia working at the interfaces of healthcare, engineering and nanotechnology.
Keywords: Nanotechnology.; Nanomedicine.; elektronické knihy; electronic books